A novel linear frequency modulation signal generator in real‐time processing of airborne synthetic aperture radar. Issue 2 (3rd February 2023) - Chen, Dongxu; Wei, Tingcun; Li, Gaoang; Zeng, Jialong; Feng, Jie; Yang, Xudong; Yu, Zhongjun
Abstract: Generally, synthetic aperture radar(SAR)generates linear frequency modulation (LFM) signals by method of look‐up table (LUT), which requires calculating different LFM signals and storing these waveforms in advance. With the demand for multi‐mode, high‐resolution and wide swath of airborne SAR systems, the method of LUT is not available, because that requires huge storage resources. In order to solve these drawbacks in limited hardware resources, this letter proposes a novel LFM signal generator in real‐time processing. By taking advantage of high level synthesis (HLS) on FPGA, the proposed generator calculates the LFM signal simply using parameters of pulse width, bandwidth, and sampling frequency. Meanwhile, in order to compensate for the SAR system phase error, the proposed generator calculates phase error using a linear polynomial algorithm, which can compensate for the phase error in real time. The simulation results prove that this approximation can achieve a good effect. The performance of this method is implemented by experiments with an X‐band airborne SAR system. Abstract : This letter proposes a novel LFM signal generator in real‐time processing. In order to compensate for the SAR system phase error, the proposed generator calculates phase error using a linear polynomial algorithm.